An evaluation of the ethical behaviour of MBA students at a selected business school - Rapule, Sello Daniel (North-West University, 2011)
Business schools have been under scrutiny over the last few years with regard to the type of manager leaders that they produce. This is because the business sector has suffered significantly, both financially and in terms of global reputation due to the unethical conduct of those in management and leadership of the organisations. The scandals that rocked the world in recent times, from business entities such as Enron and Tiger Brands provide examples of the unethical behaviour in the day–to–day running of business and further bring forth the essential need for an in–depth study in the behaviour of the manager–leaders. These manager–leaders are said to be graduates from business schools around the world. Researchers and business schools have started to put emphasis on the importance of ethical behaviour in manager–leaders. Business schools in particular have introduced and included business law and ethics as one of the modules in the curriculum of the MBA program so as to inculcate the ethical conduct in the present and emerging manager–leaders in organisations. Therefore, this study is based on the evaluation of the ethical behaviour of the MBA students at a selected business school in South Africa. The subjects of this study (MBA students) were subjected to questionnaires that prompted their convictions with regard to ethical behaviour at personal (individual) level and on company level as well. The results of the study indicated that the MBA students at this selected business school are ethical in behaviour at both individual and company levels, hence complied with principles that are guidelines in the renowned King reports. However, a comparative study with other business schools will be necessary so as to measure the relative ethical behaviour of the MBA students at other business schools.
Thesis (M.B.A.)--North-West University, Potchefstroom Campus, 2012.
Keywords: Business school ethics; MBA; Managerial ethics; Corrupt business practices; Company ethics; Code of Conduct